Multicultural Education and Interreligious Leaders Knowledge - Marjuni Marjuni (Institut Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2014)
Multicultural-education is meant to portray about the efforts that must be carried out by teachers and lecturers in the midst of a growing cultural diversity in today's society. Teachers and lecturers are expected to contribute in revising the learning material as well as to reform the learning system with wider insight in the globalization process. The birth of various teachings or understandings which are not relevant with religious values, such as secularism and materialism, tends to make religion education to be helpless and even to make religion to be ruled out in various fields. This may also hit people when religion does no longer function effectively in multidimensional and multicultural life.